Analysis of antidiabetic drug utilization patterns in type 2 diabetes patients: a perspective on real-time prescribing practices - Surajo, Bashir; Khan, Ziyaurrahman; Shadab, M.; Khan, Naureen; Sada, Mudassir; Ahmad, Mohammad; Akhter, M. Sohel; Parveen, Ayasa (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Type 2 diabetes is a most common health problem associated with significant morbidity and mortality worldwide, evaluation of drug utilization pattern is very crucial and significant in order to promote the rational use of drugs in treatment of diabetes, and offer insights in to the actual patterns of drug use. The objective is to evaluate drug utilization pattern of antidiabetic drugs among type 2 diabetic patients at Integral Institute of Medical Science & Research. Methods: This is a prospective observational study involving 100 subjects conducted for a period of 6 months after approval by Institutional Ethics Committee (IEC) of Integral University at IIMS and R Hospital. Informed consent was obtained from all the participants. Data gathered was examined using descriptive statistics and compared to the standard guidelines. Drug utilization pattern was studied and evaluated to analyse the pattern of drug therapy among type 2 diabetics. Results: Antidiabetic drugs were given 198 times among the 100 participants, averaging 2 antidiabetic drugs per prescription, Insulin therapy (58.58%) and Metformin (20.20%) were the most prescribed medications, combination therapy was common, with 66% of patients particularly with Glimepiride (DPP4 Inhibitor) at 10.61%. Most prescriptions were given by generic name (55%) and 90% of the drugs prescribed were from the WHO essential medicines. Most patients were aged 51-60 years, with a nearly equal gender distribution. Conclusion: The study highlights the prescribing patterns and characteristic use of antidiabetic medications. These findings provide valuable insights into the current prescribing practices in type-2 DM treatment and can contribute to optimizing treatment strategies for better patient outcomes.